Effect of spacer groups on the performance of MCM-41-supported platinum cluster-derived hydrogenation catalysts - Maity, Niladri; Basu, Susmit; Mapa, Maitri; Rajamohanan, Pattuparambil R.; Ganapathy, Subramanian; Gopinath, Chinnakonda S.; Bhaduri, Sumit; Lahiri, Goutam Kumar (Journal of Catalysis, 2006)
MCM-41 was functionalized with (EtO)(3)SiCH2Cl, (MeO)(3)SiCH2CH2CH2Cl, and (CH3)Cl2SiCH2Cl. The functionalized materials were characterized by solid-state NMR (CPMAS, Si-29 and C-13) and XPS. The NMR data indicate that three new silicon environments were created by(EtO)(3)SiCH2Cl and (MeO)(3)SiCH2CH2CH2Cl, whereas with (CH3)Cl2SiCH2Cl, two new silicon environments were obtained. XPS results from Si 2p core level and the valence band from the material functionalized by (MeO)(3)Si(CH2)(3)Cl was found to be the same as that of the corresponding fresh catalyst (1a), in contrast to that of the materials functionalized by the other two silane reagents. After further functionalization with triethylamine, these materials were used as inorganic anion exchangers to support the cluster anion [Pt-12(CO)(24)](2-). Solid-state NMR (29Si, C-13, N-15) was used to establish the presence of the quaternary ammonium group in the cluster-supported species. Analogous materials were also created using fumed silica as the support, and all of the cluster-supported materials were tested as catalysts for the hydrogenation of methyl pyruvate, acetophenone, nitrobenzene, benzonitrile, ethylacetoacetate, 4-nitrotoluene, cyclohexanone, allyl alcohol, and styrene. The best activity was obtained for the catalyst that had MCM-41 as the support and chloropropyl as the spacer group. TEM showed that the supports and the spacer groups had observable effects on the platinum crystallite size of the catalysts. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: functionalized inorganic oxides; hydrogenation catalysts; MCM-41; platinum carbonyl cluster; Solid-state NMR; spacer groups; XPS

Foldamers with unusual structural architecture from spirobi(indane) building blocks - Kendhale, Amol M.; Gonnade, Rajesh G.; Rajamohanan, Pattuparambil R.; Hofmann, Hans-Joerg; Sanjayan, Gangadhar J. (Chemical Communications, 2008)
This communication demonstrates the utility of inherently rigid building blocks such as 1,1'-spirobi(indane) for generating conformationally ordered synthetic oligomers with structural architectures distinct from those classically observed.

MCM-41-supported organometallic-derived nanopalladium as a selective hydrogenation catalyst - Maity, Niladri; Rajamohanan, Pattuparambil R.; Ganapathy, Subramanian; Gopinath, Chinnakonda S.; Bhaduri, Sumit; Lahiri, Goutam Kumar (Journal of Physical Chemistry C, 2008)
Palladium nanocatalysts have been prepared by anchoring (eta(3)-C(3)H(5))(2)Pd(2)Cl(2) onto dian-tine-functionalized MCM-41 supports followed by reaction with hydrogen under catalytic conditions. The catalyst precursor and used catalyst have been studied by solid-state NMR ((13)C, (29)Si), XPS, and TEM. The organometallic-derived catalyst exhibits the best performance (activity and selectivity) to date toward the selective hydrogenation of industrially relevant o- and m-chloronitrobenzene to the corresponding chloroaniline derivatives and is distinctly superior to 5% Pd/C. Grazing angle XPS studies reveal that conversion of the tethered molecular species to the nanoparticles of palladium produces a core-shell nanostructure.

Concurrent display of both alpha- and beta-turns in a model peptide - Srinivas, Deekonda; Vijayadas, Kuruppanthara N.; Gonnade, Rajesh G.; Phalgune, Usha D.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2011)
This article describes a model peptide that concurrently displays both alpha- and beta-turns, as demonstrated by structural investigations using single crystal X-ray crystallography and solution-state NMR studies. The motif reported herein has the potential for the design of novel conformationally ordered synthetic oligomers with structural architectures distinct from those classically observed.

Selective hydrogenation of chloronitrobenzenes with an MCM-41 supported platinum allyl complex derived catalyst - Indra, Arindam; Rajamohanan, Pattuparambil R.; Gopinath, Chinnakonda S.; Bhaduri, Sumit; Lahiri, Goutam Kumar (Applied Catalysis A-General, 2011)
A platinuin precatalyst (1) has been prepared by reacting [(eta(3)-C3H5)(4)Pt4Cl4] with surface functionalized MCM-41 with pendant -(CH2)(3)NH(CH2)(2)NH2 groups. For the hydrogenation of o-, m- and p-chloronitrobenzenes to the corresponding chloroanilines, 1 is found to be a highly active catalyst with good selectivities for them-and p-isomers. Its performance is superior to that of its palladium analogue and far superior to that of commercial (5%) Pt/C or (5%) Pt/Al2O3. Comparison of solid state and solution NMR data and other evidences indicate that on treatment with the functionalized MCM-41 support; [(eta(3)-C3H5)(4)Pt4Cl4] loses the ally! ligand. XPS data show that in the fresh catalyst Pt is present in the 2+ oxidation state. Based on these and analytical data, co-ordination by surface diamine and hydroxo groups to Pt2+ in 1 is suggested. In the used catalyst both Pt2+ and Pt are present but the amount of metallic platinum is similar to 16% of the total. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Chloronitrobenzenes; Dehydrohalogenation; heterogeneous catalyst; MCM-41; Selective hydrogenation

Synthesis and structural characterization of homochiral homo-oligomers of parent CIS- and trans-furanoid-beta-amino acids - Pandey, Sunil K.; Jogdand, Ganesh F.; Oliveira, Joao C. A.; Mata, Ricardo A.; Rajamohanan, Pattuparambil R.; Ramana, Chepuri V. (Chemistry-A European Journal, 2011)
The synthesis of homochiral homo-oligomers of cis- and trans-3-aminotetrahydrofuran-2-carboxylic acids (parent cis- and trans-furanoid-beta-amino acids, referred to as ``cis-/trans-FAA'') has been carried out to understand their secondary structures and their dependence on the ring heteroatom. The oligomers of two diastereomers have been shown to have a distinct left-handed helicity. The cis-FAA homo-oligomers show a 14-helix structure, in contrast to the homo-oligomers of cis-ACPC, which adopt a sheet like structure. The trans-FAA homo-oligomers were found to adopt a 12-helix structure, the same trend found in trans-ACPC homo-oligomers. With the help of ab initio calculations, the structural features of cis-ACPC and cis-FAA hexamers were compared. We believe that the more compact packing of the cis-FAA hexapeptide should be due to a more favorable interaction between the ring and the backbone amide hydrogen.
Keywords: ab initio calculations; Amino acids; Density functional calculations; Peptides; secondary structures

Helical folding in heterogeneous foldamers without inter-residual backbone hydrogen-bonding - Priya, Gowri; Kotmale, Amol S.; Gawade, Rupesh L.; Mishra, Deepti; Pal, Sourav; Puranik, Vedavati G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Chemical Communications, 2012)
This communication describes a set of hybrid foldamers that do not feature inter-residual, but intra-residual backbone hydrogen-bonding, yet adopt a preferentially folded conformation displaying right-handed helical architecture. Conformational ordering is apparently due to the combined conformational restrictions imposed by the conformationally restricted individual amino acid residues with which the oligomers are made of.

Multifaceted folding in a foldamer featuring highly cooperative folds - Ramesh, Veera V. E.; Priya, Gowri; Kotmale, Amol S.; Gonnade, Rajesh G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Chemical Communications, 2012)
Herein, we report on the folding pattern observed in a synthetic peptide featuring two highly mutually dependent, yet strikingly dissimilar, closed networks of hydrogen-bonded rings that work in a cumulative fashion to stabilize the entire folded architecture of the peptide. Structural studies unequivocally suggest that disruption of any one of these mutually-dependent hydrogen-bonded networks is deleterious to the stability of the fully folded conformation of the peptide.

Unusual conformational similarity of two peptide folds featuring sulfonamide and carboxamide on the backbone - Vijayadas, Kuruppanthara N.; Davis, Hilda C.; Kotmale, Amol S.; Gawade, Rupesh L.; Puranik, Vedavati G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Chemical Communications, 2012)
Two folded peptides featuring carboxamide and sulfonamide at the core of the peptide fold have been shown to possess almost similar conformational features, despite the well-known fact that carboxamides and sulfonamides have strikingly different hydrogen-bonding and geometrical preferences.

Ant-pro reverse-turn motif. structural features and conformational characteristics - Thorat, Vijaykumar H.; Ingole, Tukaram S.; Vijayadas, Kuruppanthara N.; Nair, Roshna V.; Kale, Sangram S.; Ramesh, Veera V. E.; Davis, Hilda C.; Prabhakaran, Panchami; Gonnade, Rajesh G.; Gawade, Rupesh L.; Puranik, Vedavati G.; Rajamohanan, Pattuparambil R.; et al. (European Journal of Organic Chemistry, 2013)
This article details the characteristic conformational features of the Ant-Pro reverse turn ? a folded pseudo -turn motif that displays a closed nine-membered-ring hydrogen-bonded network involving just two amino acid residues, namely anthranilic acid (Ant; a constrained -amino acid), and proline (Pro; a constrained -amino acid). The results from the extensive investigation of ten crystal structures and their NMR conformations in the solution state provide a clear idea about the conformational characteristics of the Ant-Pro reverse turn. The Ant and Pro residues, which form the turn segment, maintain a perfect antiperiplanar orientation throughout, leaving little possibility for the formation of the otherwise possible six-membered hydrogen-bonding that requires a coplanar disposition of the two amino acid residues, as clearly evident from investigation of several crystal structures. The closed hydrogen-bonded network observed in the Ant-Pro reverse turn motif, formed in the forward direction of the sequence (12 amino acid interactions) involving only two amino acid residues, is in stark contrast to the native -turns that involve four residues to form hydrogen-bonded network featuring backward 14 amino acid interactions. The readily available two-residue Ant-Pro motif raises the possibility of a practical utility, particularly in the application of rigidifying flexible peptide backbones by inserting the robust Ant-Pro reverse turn motifs into their backbone.
Keywords: Peptides; Peptidomimetics; Protein folding; Protein structures

Ester vs. amide on folding: a case study with a 2-residue synthetic peptide - Vijayadas, Kuruppanthara N.; Nair, Roshna V.; Gawade, Rupesh L.; Kotmale, Amol S.; Prabhakaran, Panchami; Gonnade, Rajesh G.; Puranik, Vedavati G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2013)
Although known for their inferiority as hydrogen-bonding acceptors when compared to amides, esters are often found at the C-terminus of peptides and synthetic oligomers (foldamers), presumably due to the synthetic readiness with which they are obtained using protected peptide coupling, deploying amino acid esters at the C-terminus. When the H-bonding interactions deviate from regularity at the termini, peptide chains tend to ``fray apart''. However, the individual contributions of C-terminal esters in causing peptide chain end-fraying goes often unnoticed, particularly due to diverse competing effects emanating from large peptide chains. Herein, we describe a striking case of a comparison of the individual contributions of C-terminal ester vs. amide carbonyl as a H-bonding acceptor in the folding of a peptide. A simple two-residue peptide fold has been used as a testing case to demonstrate that amide carbonyl is far superior to ester carbonyl in promoting peptide folding, alienating end-fraying. This finding would have a bearing on the fundamental understanding of the individual contributions of stabilizing/destabilizing non-covalent interactions in peptide folding.

Switching the H-bonding network of a foldamer by modulating the backbone chirality and constitutional ratio of amino acids - Ramesh, Veera V. E.; Vijayadas, Kuruppanthara N.; Dhokale, Snehal A.; Gonnade, Rajesh G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2013)
This communication describes the folding propensity of a hetero-foldamer motif featuring proline (Pro) and anthranilic acid (Ant) residues in a 1:2:1 (alpha: beta: alpha) constitutional ratio. Structural investigations unequivocally suggest that the hydrogen-bonding network of this foldamer motif can be switched between 9-membered and 6-membered by modulating the backbone chirality and constitutional ratio of the amino acid residues.

Synthetic zipper peptide motif orchestrated via co-operative interplay of hydrogen bonding, aromatic stacking, and backbone chirality - Nair, Roshna V.; Kheria, Sanjeev; Rayavarapu, Suresh; Kotmale, Amol S.; Jagadeesh, Bharatam; Gonnade, Rajesh G.; Puranik, Vedavati G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Journal of the American Chemical Society, 2013)
Here, we report on a new class of synthetic zipper peptide which assumes its three-dimensional zipper-like structure via a co-operative interplay of hydrogen bonding, aromatic stacking, and backbone chirality. Structural studies carried out in both solid- and solution-state confirmed the zipper-like structural architecture assumed by the synthetic peptide which makes use of unusually remote inter-residual hydrogen-bonding and aromatic stacking interactions to attain its shape. The effect of chirality modulation and the extent of noncovalent forces in the structure stabilization have also been comprehensively explored via single-crystal X-ray diffraction and solution-state NMR studies. The results highlight the utility of noncovalent forces in engineering complex synthetic molecules with intriguing structural architectures.

Tetrazine templated method for the synthesis of ternary conjugates - Rao, Boddu Venkateswara; Dhokale, Snehal A.; Rajamohanan, Pattuparambil R.; Hotha, Srinivas (Chemical Communications, 2013)
Conjugation is an important reaction that enables coupling of molecules. Many protocols exist for the synthesis of binary conjugates from two different molecules or for the polyvalent display of a singlemolecule. There aren'tmanymethods for the synthesis of ternary conjugates. However, methods for ternary conjugation are important for understanding the interplay of interactions between three biomolecules (or any three molecules per se). A strategy for ternary bioconjugation using inverse electron demand Diels-Alder reaction with tetrazine is studied. Ternary conjugation was demonstrated by the reaction of a model glyco-peptide binary conjugate with a fluorescent tagged olefin.

Transition-metal-free multicomponent reactions involving arynes, N-heterocycles, and isatins - Bhunia, Anup; Roy, Tony; Pachfule, Pradip; Rajamohanan, Pattuparambil R.; Biju, Akkattu T. (Angewandte Chemie-International Edition, 2013)
Mix and match: With isoquinoline as the nucleophilic trigger, multicomponent reactions afforded spirooxazino isoquinoline derivatives, proceeding through 1,4-dipolar intermediates. The use of pyridine as a nucleophile furnished indolin-2-one derivatives, with the reaction likely proceeding through a pyridylidene intermediate.

Formation of a pseudo-beta-hairpin motif utilizing the Ant-Pro reverse turn: consequences of stereochemical reordering - Nair, Roshna V.; Kotmale, Amol S.; Dhokale, Snehal A.; Gawade, Rupesh L.; Puranik, Vedavati G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2014)
Herein, we report a special case of pseudo-beta-hairpin formation by tetrapetide sequences featuring a two-membered Ant Pro dipeptide motif (Ant = anthranilic acid and Pro = proline) at the loop region. These folded structures uniquely feature the presence of C9- and C17-H-bonding patterns at reverse turn and interstrand regions, respectively. Their hairpin nucleation and folding propensities have been expounded using solution and solid state studies of distinct stereochemically altered sequences.

Supramolecular transitions in native cellulose-I during progressive oxidation reaction leading to quasi-spherical nanoparticles of 6-carboxycellulose - Sharma, Priyanka R.; Rajamohanan, Pattuparambil R.; Varma, Anjanikumar (Carbohydrate Polymers, 2014)
Cellulose-I swells considerably in phosphoric acid, and converts to amorphous cellulose via a cellulose-II transition state. Controlled oxidation of cellulose-I to 6-carboxycellulose (6CC) using HNO3-H3PO4-NaNO2 oxidation system led to the selective production of 6CC's of varying carboxyl contents (1.7-22%) as well as various shapes and sizes (macro-sized fibrils of several micron length and/or spherical nanoparticles of 25-35 nm), depending on the reaction conditions. 6CC's having less than 14% carboxyl content were largely in cellulose-II form (WAXRD values in-between cellulose I and cellulose II), whereas at 14-22% the 6CC's were largely amorphous; only trace crystallinity was observed at 19% and 22% carboxyl 6CC. Spherical nanoparticles retained a high degree of crystallinity having cellulose-I structure, whereas the macro-sized fibrils were largely converted to cellulose-II structure. Analysis by WAXRD as well as by CP-MAS C-13 NMR studies gave similar conclusions. Reduced molecular weight with progressive oxidation, including presence of oligomers, was also evident from an increase in the reducing-end carbon peak at similar to 92 ppm. For high oxidation levels (>14%) the NMR 92-96 ppm peaks disappeared on extracting with dilute alkali, due to soluble oligomers being removed. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Carboxycellulose; cellulose; Nanoparticles; NMR; WAXRD

Conformational modulation of peptides using beta-amino benzenesulfonic acid ((S)Ant) - Priya, Gowri; Kotmale, Amol S.; Chakravarty, Debamitra K.; Puranik, Vedavati G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2015)
This communication describes the utility of a conformationally restricted aromatic beta-amino acid (2-aminobenzenesulfonic acid, (S)Ant) inducing various folding interactions in short peptides. Sandwiching (S)Ant between diverse amino acid residues was shown to form robust folded architectures featuring a variety of H-bonded networks, suggesting its utility in inducing peptide folding.

Reversal of H-bonding direction by N-sulfonation in a synthetic reverse-turn peptide motif - Vijayadas, Kuruppanthara N.; Kotmale, Amol S.; Thorat, Shridhar H.; Gonnade, Rajesh G.; Nair, Roshna V.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2015)
This communication depicts an intriguing example of hydrogen-bonding reversal upon introduction of a sulfonamide linkage at the N-terminus of a synthetic reverse-turn peptide motif. The ready availability of two sulfonyl oxygen atoms, as hydrogen-bonding acceptors, combined with the inherent twisted conformation of sulfonamides are seen to act as switches that engage/disengage the hydrogen-bond at the sticky ends/termini.

Role of N-terminal proline in stabilizing the Ant-Pro zipper motif - Kheria, Sanjeev; Nair, Roshna V.; Kotmale, Amol S.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (New Journal of Chemistry, 2015)
Hetero-chiral hybrid peptides of the general sequence (L)alpha beta(D)(n)alpha beta(n) featuring proline (Pro, a constrained alpha-amino acid) and anthranilic acid (Ant, a constrained beta-amino acid) as building blocks, where n = 2, 4 etc., form a three-dimensional zipper-like architecture. These zipper peptides attain stable conformation by balancing the co-operative contribution of two competing non-covalent forces, namely hydrogen bonding and aromatic stacking. However, the selection of the N-terminal residue also stands to be one of the key contributors in stabilising the unusually long-range intramolecular hydrogen bond, featuring 26 atoms in the H-bonded ring observed at the termini. This article deals with the substitution alterations at the N-terminus of the zipper motif and their consequent influences on its structure and stability. In this study, the N-terminal Pro residue of the zipper motif was substituted with a flexible amino acid, alanine, and a constrained acyclic amino acid, 2-aminoisobutyric acid, to investigate the role of N-terminal proline in stabilizing the Ant-Pro zipper motif, and its stabilities were assessed by employing solution-state NMR and restrained MD simulation studies.

3-Aminothiophenecarboxylic acid (3-Atc)-induced folding in peptides - Ingole, Tukaram S.; Kotmale, Amol S.; Gawade, Rupesh L.; Gonnade, Rajesh G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (New Journal of Chemistry, 2016)
This paper describes the consequences of incorporating a constrained heterocyclic aromatic b-amino acid 3-aminothiophenecarboxylic acid (3-Atc) into peptides containing beta-turn forming elements such as Pro-Gly motif and the effect on the secondary structural architecture of the entire peptide backbone. Conformational investigations of oligomers comprising an alpha,beta,alpha peptide sequence were carried out by single-crystal X-ray diffraction, solution-state NMR, nOe-restrained MD simulation and circular dichroism studies. The results suggested that these peptide sequences assume helical architecture. The helical folding in the oligomers was found to be devoid of inter-residual H-bonding, instead found to be stabilized by a co-operative effect of 6-membered H-bonding within the 3-Atc unit and conformational restrictions of individual amino acids in the peptide backbone.

Additive mediated syn-anti conformational tuning at nucleation to capture elusive polymorphs: remarkable role of extended pi-stacking interactions in driving the self-assembly - Gawade, Rupesh L.; Chakravarty, Debamitra K.; Kotmale, Amol; Sangtani, Ekta; Joshi, Pranaya V.; Ahmed, Awais; Mane, Manoj V.; Das, Susanta; Vanka, Kumar; Rajamohanan, Pattuparambil R.; Puranik, Vedavati G.; Gonnade, Rajesh G. (Crystal Growth & Design, 2016)
Understanding the process of prenucleation clustering at supersaturating stage is of significant importance to envisage the polymorphism in crystalline materials. Preferential formation of a thermodynamically stable crystal form suggests energetically favored patterns of interactions which control molecular aggregation during nucleation. Introduction of additives during crystallization is sometimes used as a suitable strategy to obtain metastable polymorphs in cases where it is not easy to capture the same by conventional crystallization methods. Comparative analysis of energy relationships and intermolecular interactions between thermodynamically stable and metastable crystal forms provides valuable clues about the nature of growth synthons at prenucleation clustering and preferential crystallization of the thermodynamic form. Conformationally flexible sulfonamide/sulfoester derivatives constituting electron rich and electron deficient aromatic rings were synthesized to study the interplay between pi-stacking and hydrogen bonding synthons. We have identified and characterized the thermodynamically stable and metastable elusive polymorphs of aromatic sulfonamides 1 and 2 and sulfoesters 3 and 4. However, these compounds eluded polymorphism during crystallisation from various common solvents/conditions and only produced thermodynamically stable crystals forms (form I crystals). Surprisingly, exploitation of pyrazinamide as an additive in different stoichiometric ratios during crystallization gave elusive polymorphs [three for 1 (form 1II, form 1III, and form 1IV) and one each for 2 (form 2II), 3 (form 3II), and 4 (form 4II)]. Molecules in stable crystal forms of these compounds are linked via extended chains of parallel displaced pi...pi stacking interactions that seem to play a vital role in driving the self-assembly of molecules and subsequently governing the nucleation process. In contrast, molecules in metastable polymorphs are devoid of such extended pi-stacking assemblies. Interestingly, differential scanning calorimetry, hot stage microscopy, and X-ray crystallographic studies confirmed the thermal crystal-to-crystal transition of all three metastable polymorphs of 1 (form 1II, form 1III, and form 1IV) to its thermodynamically stable crystal form (form 1I). Conformational analysis of molecule 1 using density functional theory calculations also validated higher stability for syn conformation (observed in Form 1I crystals) over anti and midway conformations (seen in metastable polymorphs). Melt crystallization of form 1I crystals of 1 on the larger face (001) of delta-pyrazinamide and lattice matching analysis (GRACE) revealed that the layered arrangement of molecules of delta-pyrazinamide (on 001 face) during heterogeneous nucleation acts as a template (heteroepitaxy) to provide a preferential site for the nucleation of new metastable polymorphs by selectively inhibiting the most preferred crystal form from growing into the nucleus. Solution state one- and two-dimensional (NOESY) H-1 NMR, scanning electron microscopy, and a Cambridge Structural Database survey were conducted to substantiate the role of additives during crystallization.

Angiotensin II analogs comprised of pro-amb (gamma-turn scaffold) as angiotensin II type 2 (AT(2)) receptor agonists - Jedhe, Ganesh S.; Kotmale, Amol S.; Rajamohanan, Pattuparambil R.; Pasha, Santosh; Sanjayan, Gangadhar J. (Chemical Communications, 2016)
We describe herein the design, synthesis and conformational investigation of Pro-Amb (proline-3-amino-2-methoxybenzoic acid) incorporated Angiotensin II and its truncated analogues. Solution-state NMR and CD studies suggest gamma-turn-like conformation in Pro-Amb analogs in aqueous solution. Furthermore, Pro-Amb analogs have been shown to act as AT(2) receptor agonists.

Oxidative intramolecular 1,2-amino-oxygenation of alkynes under Au(I)/Au(III)-catalysis: discovery of pyridinium-oxazole dyad as novel lonic fluorophore - Shaikh, Aslam C.; Ranade, Dnyanesh S.; Rajamohanan, Pattuparambil R.; Kulkarni, Prasad P.; Patil, Nitin T. (Angewandte Chemie International Edition, 2016)

Residue dependent hydrogen-bonding preferences in orthanilic acid-based short peptide beta-turn motifs - Jedhe, Ganesh S.; Vijayadas, Kuruppanthara N.; Kotmale, Amol S.; Sangtani, Ekta; Shinde, Dinesh R.; Gonnade, Rajesh G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (RSC Advances, 2016)
This communication describes the competition between native beta-turn (C10) and 2-aminobenzenesulfonic acid (SAnt)( orthanilic acid)-based pseudo beta-turn (C11) in their hybrid peptides. Solid-state crystal structure and solution-state NMR studies revealed that C10 and C11 can be simultaneously observed under appropriate conditions. The variable temperature NMR coefficient data suggest that the isolated C11/C14 hydrogen bond is weaker in comparison with the consecutive C10 and C11 turns.

Silk fibroin-sophorolipid gelation: deciphering the underlying mechanism - Dubey, Parul; Kumar, Sugam; Aswal, Vinod K.; Ravindranathan, Sapna; Rajamohanan, Pattuparambil R.; Prabhune, Asmita; Nisal, Anuya (Biomacromolecules, 2016)
Silk fibroin (SF) protein, produced by silkworm Bombyx mori, is a promising biomaterial, while sophorolipid (SL) is an amphiphilic functional biosurfactant synthesized by nonpathogenic yeast Candida bombicola. SL is a mixture of two forms, acidic (ASL) and lactonic (LSL), which when added to SF results in accelerated gelation of silk fibroin. LSL is known to have multiple biological functionalities and hence hydrogels of these green molecules have promising applications in the biomedical sector. In this work, SANS, NMR, and rheology are employed to examine the assembling properties of individual and mixed SLs and their interactions with SF to understand the mechanism that leads to rapid gelation. SANS and NMR studies show that ASL assembles to form charged micelles, while LSL forms micellar assemblies and aggregates of a mass fractal nature. ASL and LSL together form larger mixed micelles, all of which interact differently with SF. It is shown that preferential binding of LSL to SF causes rapid unfolding of the SF chain leading to the formation of intermolecular beta sheets, which trigger fast gelation. Based on the observations, a mechanism for gelation of SF in the presence of different sophorolipids is proposed.

Tuning emission responses of a triphenylamine derivative in host-guest complexes and an unusual dynamic inclusion phenomenon - Gangopadhyay, Monalisa; Mandal, Amal K.; Maity, Arunava; Ravindranathan, Sapna; Rajamohanan, Pattuparambil R.; Das, Amitava (Journal of Organic Chemistry, 2016)
A newly synthesized triphenylamine derivative (1Cl(3)) shows significant differences in inclusion complex formation with two different macrocyclic hosts, cucurbit[7]uril (CB[7]) and beta-cyclodextrin (beta-CD). Detailed investigations by NMR spectroscopy reveal that CB[7] forms a 1:3 host-guest complex ([1 center dot 3{CB[7]}]Cl-3) in which three arms of 1Cl(3) are bound to three host molecules. On the other hand, beta-CD forms a dynamic 1:1 inclusion complex ([1 center dotbeta-CD]Cl-3) by binding to only one of the three arms of 1Cl(3) at a given time. The formation of a 1:1 host-guest complex with beta-CD and 1:3 host-guest complex with CB[7] was also confirmed from the results of the isothermal titration calorimetric studies. Interestingly, 1Cl(3) exhibits a rare dual emission property in solution at room temperature with the lower and higher energy bands arising from a locally excited state and an intramolecular charge-transfer transition, respectively. The difference in inclusion complex formation behavior of 1Cl(3) with the two macrocyclic hosts results in the stabilization of different emission states in the two inclusion complexes. The fundamental difference in the electrostatic surface potentials, cavity polarities, and shapes of the two macrocyclic hosts could account for the formation of the different inclusion complexes with distinct luminescence responses.

Cucurbit[7]uril induced formation of fret-enabled unilamellar lipid vesicles - Kushwaha, Shilpi; Maity, Arunava; Gangopadhyay, Monalisa; Ravindranathan, Sapna; Rajamohanan, Pattuparambil R.; Das, Amitava (Langmuir, 2017)
A unique fluorescence resonance energy transfer (FRET) process is found to be operational in a unilamellar lipid self-assembly in the aqueous phase. A newly synthesized naphthyl based long chain lipid derivative [N-(naphthalene-1-ylmethyl)tetradecane-1-ammonium chloride, 14NA(+)] forms various self-assembled architectures in the aqueous phase. Controlled changes in lipid concentration lead to a transition of the self-assemblies from micelles to vesicles to rods. In the presence of cucurbit[7]uril (CB7), 14NA(+) forms a host-guest [2]pseudorotaxane complex (CB7(sic)14NA(+)) and secondary interactions lead to the formation of a lipid bilayer with hydrophobic pockets situated in between the layers. The change in the structure of 14NA(+) assemblies, interaction with CB7 and formation of supramolecular assemblies of CB7(sic)14NA(+) were examined using light scattering, spectroscopic, and microscopic techniques. Entrapment of a luminescent dye, anthracene within the hydrophobic bilayer of the supramolecular assembly CB7(sic)14NA(+) favors a modified luminescent response due to an efficient FRET process. Further, the FRET process could be controlled by thermal and chemical stimuli that induce transformation of unilamellar vesicles.

Oxidative intramolecular 1,2-amino-oxygenation of alkynes under Au I /Au III catalysis: discovery of a pyridinium-oxazole dyad as an ionic fluorophore - Shaikh, Aslam C.; Ranade, Dnyanesh Sadanand; Rajamohanan, Pattuparambil R.; Kulkarni, Prasad Padmakar; Patil, Nitin T. (Angewandte Chemie‐International Edition, 2017)

Oxidative intramolecular 1,2-amino-oxygenation of alkynes under Au-I/Au-III catalysis: discovery of a pyridinium-oxazole dyad as an ionic fluorophore - Shaikh, Aslam C.; Ranade, Dnyanesh S.; Rajamohanan, Pattuparambil R.; Kulkarni, Prasad P.; Patil, Nitin T. (Angewandte Chemie-International Edition, 2017)
Oxidative intramolecular 1,2-amino-oxygenation reactions, combining gold(I)/gold(III) catalysis, is reported. The reaction provides efficient access to a structurally unique ionic pyridinium-oxazole dyad with tunable emission wavelengths. The application of these fluorophores as potential biomarkers has been investigated.

Reactivity of difunctional polar monomers and ethylene copolymerization: a comprehensive account - Gaikwad, Shahaji R.; Deshmukh, Satej S.; Koshti, Vijay S.; Poddar, Suparna; Gonnade, Rajesh G.; Rajamohanan, Pattuparambil R.; Chikkali, Samir H. (Macromolecules, 2017)
A comprehensive picture of insertion of 1,1-disubstituted difunctional olefins, their ability to double the functional group density at the same level of incorporation as that of monofunctional olefin, and copolymerization with ethylene has been demonstrated. Exposure of a palladium complex [P boolean AND OPdMe(L)] (P boolean AND O = kappa(2)-P,O-Ar2PC6H4SO2O with Ar = 2-MeOC6H4.; L = C2H6OS) to methyl 2-acetamidoacrylate (MAAA) revealed slight preference for 1,2-insertion over 2,1-insertion (1.0:0.7). In contrast, insertion of electron-deficient 2-(trifluoromethyl)acrylic acid (TFMAA) unveiled selective 2,1-insertion {via [(P boolean AND O)PdC5H6F3O2] (11)1. The unstable intermediate 11 undergoes beta-hydride and beta-fluoride elimination to produce subsequent insertion and elimination products. The identity of elimination products (E/Z)-2-trifluoromethyl)but-2-enoic acid [17(E/Z)] and 2-(difluoromethylene)butanoic acid (13) was fully established by 1-2D NMR spectroscopy. These insertion experiments, taken together with insertion rates, suggest that MAAA and TFMAA. are amenable to insertion. Polymerization of ethylene with MAAA, TFMAA, acetamidoacrylic acid, 2-bromoacrylic acid, dimethyl allylmalonate, and allylmalonic acid was catalyzed by [P boolean AND OPdMe(L)] (L = C2H3N) (S.ACN), and the highest incorporation of 11.8% was observed for dimethyl allylmalonate (DMAM). The changes in the surface properties of the copolymers after incorporation of difunctional olefins were evaluated by measuring the water contact angle. Copolymer with highest (11.8% of DMAM) incorporation revealed a reduced water contact angle of 76 degrees. These findings demonstrate that 1,1-disubstituted difunctional olefins are amenable to polymerization, and incorporation of difunctional olefins In polyethylene backbone leads to the production of relatively hydrophilic polyethylene copolymers.

Secondary interactions arrest the hemiaminal intermediate to invert the modus operandi of schiff base reaction: a route to benzoxazinones - Patel, Ketan; Deshmukh, Satej S.; Bodkhe, Dnyaneshwar; Mane, Manoj; Vanka, Kumar; Shinde, Dinesh; Rajamohanan, Pattuparambil R.; Nandi, Shyamapada; Vaidhyanathan, Ramanathan; Chikkali, Samir H. (Journal of Organic Chemistry, 2017)
Discovered by Hugo Schiff, condensation between amine and aldehyde represents one of the most ubiquitous reactions in chemistry. This classical reaction is widely used to manufacture pharmaceuticals and fine chemicals. However, the rapid and reversible formation of Schiff base prohibits formation of alternative products, of which benzoxazinones are an important class. Therefore, manipulating the reactivity of two partners to invert the course of this reaction is an elusive target. Presented here is a synthetic strategy that regulates the sequence of Schiff base reaction via weak secondary interactions. Guided by the computational models, reaction between 2,3,4,5,6-pentafluoro-benzaldehyde with 2-amino-6methylbenzoic acid revealed quantitative (99%) formation of 5-methyl-2-(perfluoropheny01,2-dihydro-4H-benzo[d][1,3]oxazin-4-one (15). Electron donating and electron withdrawing ortho-substituents on 2-aminobenzoic acid resulted in the production of benzoxazinones 936. The mode of action was tracked using low temperature NMR, IN vis spectroscopy, and isotopic (O-18) labeling experiments. These spectroscopic mechanistic investigations revealed that the hemiaminal intermediate is arrested by the hydrogen-bonding motif to yield benzoxazinone. Thus, the mechanistic investigations and DFT calculations categorically rule out the possibility of in situ imine formation followed by ring-closing, but support instead hydrogen-bond assisted ring-closing to prodrugs. This unprecedented reaction represents an interesting and competitive alternative to metal catalyzed and classical methods of preparing benzoxazinone.

Self-assembly of fluorinated sugar amino acid derived alpha,gamma-cyclic peptides into transmembrane anion transport - Burade, Sachin S.; Saha, Tanmoy; Bhuma, Naresh; Kumbhar, Navanath; Kotmale, Amol; Rajamohanan, Pattuparambil R.; Gonnade, Rajesh G.; Talukdar, Pinaki; Dhavale, Dilip D. (Organic Letters, 2017)
Syntheses of fluorinated sugar amino acid derived alpha,gamma-cyclic tetra- and hexapeptides are reported. The IR, NMR, ESI-MS, CD, and molecular modeling studies of cyclic tetra- and hexapeptides showed C-2 and C-3 symmetric flat oval- and triangular-ring shaped, beta-strand conformations, respectively, which appear to self assemble into nanotubes. The alpha,gamma-cyclic hexapeptide (EC50 = 2.14 mu M) is found to be a more efficient ion transporter than alpha,gamma-cyclic tetrapeptide (EC50 = 14.75 mu M). The anion selectivity and recognition of alpha,gamma-cyclic hexapeptide with NO3- ion is investigated.

Conformational studies of Ant-Pro motif-incorporated cyclic peptides: gramicidin S and avellanin - Kotmale, Amol S.; Sangtani, Ekta; Gonnade, Rajesh G.; Sarkar, Dhiman; Burade, Sachin; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (New Journal of Chemistry, 2018)
This paper reports conformational changes observed in cyclic bioactive peptides such as gramicidin S and avellanin upon incorporation of a pseudo-beta (C9) Ant-(D)Pro turn motif in their structural frameworks. Solution-state studies suggested that a synthetic gramicidin S analog exhibits a beta-sheet conformation with C9 and C17 intramolecular hydrogen bonding patterns, while its truncated analog disturbs the beta-sheet conformation. Structural details were obtained using a combination of CD studies, X-ray crystal structure studies and nOe-based MD simulation studies.

pH dependent sophorolipid assemblies and their influence on gelation of silk fibroin protein - Dubey, Parul; Kumar, Sugam; Ravindranathan, Sapna; Vasudevan, Sahana; Aswal, Vinod K.; Rajamohanan, Pattuparambil R.; Nisal, Anuya; Prabhune, Asmita (Materials Chemistry and Physics, 2018)
Sophorolipid (SL), a bio-derived surfactant is an excellent gelling agent for natural fibrous protein, silk fibroin (SF) leading to potential biomedical applications. Interaction of SF with SL has been shown to accelerate the formation of hydrogel with the rate being dependent on the form of SL used. Here, we examine the effect of pH on SL-SF interaction and gel formation by employing rheology, fluorescence spectroscopy, SANS and NMR. The results indicate that the size of SL assemblies decrease as pH increases from acidic to alkaline and significantly impacts the association of SL and SF. The association of SF and SL is mainly via hydrophobic interactions, with the SL molecules forming bead like structures along the SF chain. The increased charge on the acidic form of SL at higher pH results in greater repulsion between acidic SL molecules, which are bound to the hydrophobic sites of SF, leading to rapid chain unfolding and subsequent gelation. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Assemblies; Nuclear magnetic resonance spectroscopy; pH; Silk fibroin; Small angle neutron scattering; Sophorolipid

Self-assembly of bispentadecylphenol substituted perylenediimide with PS-b-P4VP for structure-property insight into the core of core-shell micelles - Roy, Moumita; Rajamohanan, Pattuparambil R.; Ravindranathan, Sapna; Asha, S. K. (ACS Applied Polymer Materials, 2020)
We report the use of a ditopic molecular probe bispentadecylphenol substituted perylenediimide (PBI-PDP) to examine the molecular level self-assembly of polystyrene-b-poly(4-vinylpyridine) (PS-b-P4VP) in tetrahydrofuran (THF). A series of complexes were prepared between PS-b-P4VP copolymers with varying lengths of the 4-vinylpyridine chain and PBI-PDP. Light scattering and NMR spectroscopic studies reveal that the self-assembled structures of the solid complexes are not fully disrupted when the complexes are dissolved in THF. NMR experimental parameters measured for the small probe molecule provide detailed insights into the structure of the assemblies in solution as well as the interaction between the small molecule and the block copolymer. Such insights can have important implications in manipulating the nanostructure of block copolymer micelles to suit various application requirements. The dynamics and distribution of the PBI-PDP molecules within the assemblies in solution show a dependence on the length of the P4VP block. Transmission electron microscopy was employed to study the evolution of morphologies in films prepared from the self-assembled structures in THF solutions.
Keywords: core corona interface; ditopic molecular probe; environment; micelles; perylenediimide; PS-b-P4VP; Self-assembly

Viscoelastic behaviors of hyaluronic derivatives as a function of pH, salt, and temperature - Kadam, Yogesh; Badiger, Manohar V.; Rajamohanan, Pattuparambil R.; Wadgaonkar, Prakash P.; Ducouret, Guylaine; Merland, Theo; Hourdet, Dominique (Journal of Polymer Science, 2026)
Hyaluronic acid and its derivatives are essential polysaccharides widely used in the bio-medical field for their applications in tissue engineering and controlled drug delivery. By revisiting the wide variety of rheological behavior of aqueous hyaluronan solutions as a function of pH, we develop in this work a comparative study between solutions of native hyaluronan (HA) and its derivative (HA-PEPO) obtained by grafting onto thermoresponsive side-chains of poly(ethylene oxide-co-propylene oxide) characterized by a phase transition around body temperature. Based on a large dataset obtained at a fixed polymer concentration, by changing either the chemical composition of the chain and/or the environmental conditions (pH, temperature, added salt), we show that the viscoelastic properties of hyaluronan solutions can be controlled over more than three decades of amplitude with the possibility to get either liquid or gel states, regardless of temperature, as well as sol/gel transitions induced by cooling or heating by the interplay between hydrogen bonds, hydrophobic interactions, and cation binding induced by potassium salts.
Keywords: hyaluronan; Hydrogel; pH-induced gelation; salt-induced gelation; thermoresponsive polymers; tissue engineering